Implementasi Kaizen Dalam Proses Pasokan Instrumen Panel Upper dan Lower Pada Bagian Operasional Logistik PT. XYZ - Dzulqarnain, Dimas Lefy; Ngadono, Teguh Sri (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
Kaizen which means continuous improvement, firstly introduced by Masaaki Imai and carried out in several Japanese companies. Currently kaizen has been widely adopted by several other companies to reduce the waste that occurs. This waste can result in unnecessary costs and reduced profitability of a company. PT. XYZ is a Japanese company that has consistently implemented Kaizen to improve several production processes. Kaizen is a must in every process line in the company. In the second quarter of 2019 the company has increased production takt time to 2.0 resulting in an increase in supply of materials by 11%. However, this was not matched by readiness from the logistics of the panel instrument material supplier. This resulted in a waste of the process on the panel instrument supply line to the production process namely the transit area from the supplier to the assembly process line. It is expected that with the existence of kaizen, waste in the transit area can be eliminated along with the increase in takt time and the amount of future production. Plan Do Check Action (PDCA) cycle is a stage used by companies in controlling and managing a standard operational process. . Improvements are focused on how to make the transit area can be removed. After the kaizen was conducted, the results of calculations carried out by the Logistics team found savings in logistics operational costs of around Rp. 160,000,000 per year.